Duties and job performance factors of cataloguers in Nigerian academic libraries - Mansor, Yushiana (University of Nebraska--Lincoln Libraries, 2012)
Cataloguing is fundamentally the basis of theory of knowledge where information organisation, the structure and the means for handling them are identified and specified. Cataloguers are the specialists responsible for bibliographic control, information management and the creation of resource discovery tool that aids user in their search for materials. Essentially, they are responsible for the provision and organisation of efficient and effective retrieval system. Thereby saves time, increases the quality/productivity of library users and ultimately enhances the performance of the institution to achieve set objectives. Literatures indicated swift changes in duties, skills and functions of cataloguers. The changes had posed challenges to the professional development of cataloguers. This study with the use of questionnaire surveyed cataloguing practice in Nigeria in the twenty first century, their duties and tools being use in the university libraries. In addition it collects opinions on job performance factors. The result revealed that the libraries are of medium size collection with low cataloguers strength and modest use of ICT in all the libraries. The libraries still possess the card catalogue system. On the duties perform, eighty-six percent of the cataloguers, perform technical duties as original descriptive and subject cataloguing, determining appropriate guidelines in applying rules, Subject heading polices with the use of Subject thesaurus. Leading skills that enhanced job performance of the respondents include: Ability to plan,organise/supervise cataloguing activities in the library, Ability to establish/maintain effective work relationship with colleagues and other library staff and Ability to lead the way in researching into new techniques for cataloguing. All the libraries still engage in manual cataloguing work and uses traditional library working tools.